Computational Study of Drug kinetics in the Vitreous Humor - Seth, Deepti; Ali, Rashid; Saxena, Pinky; Sharma, Kuldeep; Pathak, Anuj (Journal of Neonatal Surgery, 2025)
A comprehensive study of drug delivery in vitreous body was analyzed and zero order reaction rate mechanism compared with first order mechanism. A simple Mathematical model was developed and numerical solution obtained by using numerical iterative techniques. The effect of various parameter elimination rate reaction, diffusion coefficient, vitreous humor volume on drug concentration was observed. Initially at a constant reaction rate the drug concentration increases linearly and after some time it decays exponentially. MATLAB and other simulation software have been instrumental in these studies, seeing to tremendous advancements in intravitreal drug kinetics modeling, many parameters are still untouched like mathematically model and simulate intravitreal drug kinetics, focusing on the comparative analysis of zero-order and first-order release mechanisms using MATLAB.